Hubungan Asupan Zat Gizi Makro, Aktivitas Fisik dan Kualitas Hidup dengan Status Gizi Karyawan Rumah Sakit Mitra Keluarga Kemayoran Jakarta - Ariyani, Tutik; Khasanah , Tri Ardianti (Media Gizi Ilmiah Indonesia, 2025)
This study aims to determine the relationship between macronutrient intake, physical activity, and quality of life with the nutritional status of employees of Mitra Keluarga Hospital Kemayoran Jakarta. This study uses a cross-sectional design with the Purposive Sampling sample method, totaling 85 people. Primary data were obtained by direct interviews; for physical activity using the WHOQOL BREF  and quality of life using GPAQ, the determination of nutritional status was obtained from the calculation of body mass index (BMI) of anthropometric data, while macronutrient intake used a 2x24-hour food recall form. The data was analyzed by the Spearman's Rank test with a confidence level of 95%. The results of the study showed that employees who had a good carbohydrate intake of 76.5%, a good protein intake of 62.4%, and a fat intake of more than 78.8% for physical activity—as many as 44.7% of the respondents were classified as high, while the quality of life in the medium category was 82.4%. The results of the statistical test of this study showed that there was no relationship between carbohydrate intake (p=0.055 r=209), protein (p=0.299 r=114), fat (p=0.191 r=0143), physical activity (p=0.816 r=0.26), and quality of life (p=0.539 r=068) with nutritional status in employees